Ethics in Ancient India: In the Specific Context of Sanskrit Texts and Human Values - panwar, kaushal (Advances in Social Sciences Research Journal, 2017)
Deontology works as a fundamental element in all fields of human life. It is explained elementarily through one of the branches of elementary knowledge. At the end, the direction and vision of deontology is the positive development of human society, which is also termed as ethics, but it needs to be understood that whether the development of consciousness of society is inclusive or related to a particular section of society is decided by the fundamental values of ‘Nitīśāstra’ or Deontology. It means that they would not be helpful in developing an inclusive society if the basic values of deontology or Nitīśāstra, are driven from the base of a feudal system, then it may not be able to develop our society. Our values will only work for inclusive growth if the roots of the system have human values. Ethical values actually differ according to not only diverse cultural and traditional practices world over, but also at national and regional levels. It is also possible that there is diversity in these values because of the class and feudal cultures could have influenced them. My study aims to keep this in mind and present this subject